2006
DOI: 10.1120/jacmp.v7i4.2273
|View full text |Cite
|
Sign up to set email alerts
|

Mechanical and dose delivery accuracy evaluation in radiosurgery using polymer gels

Abstract: The polymer gel–magnetic resonance imaging (MRI) dosimetry technique was used to evaluate the mechanical and dose delivery accuracy in Leksell gamma‐knife stereotactic radiosurgery for the treatment of multiple targets. Two different polymer gel dosimeter formulations reported in the literature were prepared in‐house. A plan for the treatment of four brain metastases (targets) was generated. It involved the delivery of four 8‐mm collimator shots using different prescription isodose lines and different prescrip… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2009
2009
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 20 publications
0
3
0
Order By: Relevance
“…An important question is the validity of the multiple matrix method, in particular, with older versions of LGP, in terms of the dose prescription to multiple targets scattered over the multiple matrices. To answer this question, Sandilos et al (9) recently used polymer gel dosimetry. In their study, dose delivery accuracy was evaluated by comparing measured dose distributions with corresponding calculations.…”
Section: Introductionmentioning
confidence: 99%
“…An important question is the validity of the multiple matrix method, in particular, with older versions of LGP, in terms of the dose prescription to multiple targets scattered over the multiple matrices. To answer this question, Sandilos et al (9) recently used polymer gel dosimetry. In their study, dose delivery accuracy was evaluated by comparing measured dose distributions with corresponding calculations.…”
Section: Introductionmentioning
confidence: 99%
“…This may indicate that R 2 values in calibration vials were smaller compared to the phantoms, suggesting that polymerization was slightly inhibited in these vials by some oxygen infiltration. Sandilos et al (2006) observed a 9% underestimation in their measurements with anoxic PABIC and VIPAR dosimeters and attributed that to the attenuation of the Plexiglas phantom walls. However, while the dosimetry was done with a Perspex phantom, they used glass vials for calibration; therefore it is also possible that the gel in the calibration vials was less affected by oxygen infiltration than the gel in the Plexiglas phantom and the observed discrepancies originated from differences in oxygen contamination between calibration vials and dosimeters.…”
Section: Notable Discrepancies Between Calibration Vials and Larger P...mentioning
confidence: 97%
“…These definitions; While creating the basic geometric structure, the collimator head and dimensions that ensure the exact fit of the model are defined. Geometric definitions of other objects are made similarly [16].…”
Section: Pmmamentioning
confidence: 99%